Single Cell Sequencing of Melanoma Brain Metastases Unveils Heterogeneity of the Tumor Microenvironment in Response to Immune Checkpoint Blockade. (16th November 2020) - Alvarez-Breckenridge, Christopher; Markson, Samuel; Stocking, Jackson; Lastrapes, Matt; Nayyar, Naema; Martinez-Lage, Maria; Suva, Mario; Sullivan, Ryan; Cahill, Daniel P; Carter, Scott; Brastianos, Priscilla
Abstract: INTRODUCTION: Immune checkpoint inhibitors (ICI) have revolutionized oncologic treatment and are now first-line therapy for metastatic melanoma. With improved systemic control, there has been increasing prevalence of patients with brain metastases. Recent evidence has demonstrated objective intracranial responses in a subset of these patients treated with ICI. We hypothesize that the response to ICI for melanoma brain metastases (MBM) is reflective of unique features within the tumor microenvironment of the brain. METHODS: A cohort of 27 patients, encompassing 8 pre- and 19 post-immunotherapy MBM underwent single cell RNA sequencing using the Smart-Seq2 protocol. The cohort includes patients with longitudinal cranial resections and simultaneously resected, spatially distinct tumors. Each tumor underwent unsupervised transcriptomic analysis, differential gene expression, inferred copy number variation, T-cell receptor (TCR) sequencing and clonotype analysis. Published extracranial melanoma single cell datasets were used to compare the tumor microenvironment of the brain and periphery in response to ICI. RESULTS: A total of 14, 027 cells (6, 189 malignant, 7, 838 non-malignant) were sequenced. Brain metastases demonstrated a heterogeneous distribution of macrophage states representing a continuum of inflammatory and immunosuppressive/pro-tumor phenotypes. Intracranial macrophages were found to be more immunosuppressive than their extracranial counterparts. MBM also included a distribution of reactive neutrophils and astrocytes. Analysis across pre- and post-treatment MBM demonstrated an increase in clonally expanded T cells following ICI. Across longitudinal brain metastases collected from the same patients, there was evidence of identical T cell clones across timepoints and locations. CONCLUSION: Single cell sequencing of MBM provides insights into the cellular composition of the tumor and microenvironment. Our data suggest the cellular heterogeneity within MBM is unique when compared to extracranial disease. Additionally, T cell clonal expansion is found following ICI and T cells of the same clonotype infiltrate spatially and temporally separated brain metastases. These findings raise potential therapeutic implications as we learn to target the differential features of the innate and adaptive immune system within brain metastases and their extracranial counterparts.